Association of CD30 transcripts with Th1 responses and proinflammatory cytokines in patients with end-stage renal disease - Velásquez, Sonia Y.; Opelz, Gerhard; Rojas, Mauricio; Süsal, Caner; Alvarez, Cristiam M. (Human immunology, 2016)
High serum sCD30 levels are associated with inflammatory disorders and poor outcome in renal transplantation. The contribution to these phenomena of transcripts and proteins related to CD30-activation and -cleavage is unknown. We assessed in peripheral blood of end-stage renal disease patients (ESRDP) transcripts of CD30-activation proteins CD30 and CD30L, CD30-cleavage proteins ADAM10 and ADAM17, and Th1- and Th2-type immunity-related factors t-bet and GATA3. Additionally, we evaluated the same transcripts and release of sCD30 and 32 cytokines after allogeneic and polyclonal T-cell activation. In peripheral blood, ESRDP showed increased levels of t-bet and GATA3 transcripts compared to healthy controls (HC) (both P<0.01) whereas levels of CD30, CD30L, ADAM10 and ADAM17 transcripts were similar. Polyclonal and allogeneic stimulation induced higher levels of CD30 transcripts in ESRDP than in HC (both P<0.001). Principal component analysis (PCA) in allogeneic cultures of ESRDP identified two correlation clusters, one consisting of sCD30, the Th-1 cytokine IFN-γ, MIP-1α, RANTES, sIL-2Rα, MIP-1β, TNF-β, MDC, GM-CSF and IL-5, and another one consisting of CD30 and t-bet transcripts, IL-13 and proinflammatory proteins IP-10, IL-8, IL-1Rα and MCP-1. Reflecting an activated immune state, ESRDP exhibited after allostimulation upregulation of CD30 transcripts in T cells, which was associated with Th1 and proinflammatory responses.
Gesehen am 04.06.2020